2013
DOI: 10.7556/jaoa.2013.037
|View full text |Cite
|
Sign up to set email alerts
|

Mucormycosis in a Patient With AIDS Receiving Systemic Steroids

Abstract: Mucormycosis is an opportunistic fungal infection with a high mortality rate. Although mucormycosis is relatively rare, recent studies suggest that the incidence is on the rise as a result of increased use of chemotherapy and steroids. The authors present an unusual case of invasive mucormycosis in a hospitalized patient with AIDS who was receiving short-term, high-dose steroids and who had associated steroid-induced diabetes. The patient was otherwise healthy, with no underlying risk factors such as neutropen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…24 Also, cases of mucormycosis that received corticosteroids during COVID-19 treatment are shown to be associated with poorer outcomes. 25 Sen et al reported that in their series of patients of ROCM, 98% of the patients who developed ROCM showing complete ptosis of the left eye. Magnetic resonance imaging with contrast was performed which showed diffuse intraconal fat stranding, optic nerve enhancement and ill-defined soft tissue lesion at the orbit in (B).…”
Section: Discussionmentioning
confidence: 97%
“…24 Also, cases of mucormycosis that received corticosteroids during COVID-19 treatment are shown to be associated with poorer outcomes. 25 Sen et al reported that in their series of patients of ROCM, 98% of the patients who developed ROCM showing complete ptosis of the left eye. Magnetic resonance imaging with contrast was performed which showed diffuse intraconal fat stranding, optic nerve enhancement and ill-defined soft tissue lesion at the orbit in (B).…”
Section: Discussionmentioning
confidence: 97%
“…Undoubtedly, the rush use of glucocorticoids in patients with COVID-19 has contributed to the outbreaks of COVID-19-associated mucormycosis [ 6 , 40 ]. Glucocorticoid-induced immunosuppression, hyperglycemia, and lymphopenia predispose to the pathogenesis of mucormycosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, when suspecting mucormycosis, it is important to assess by appropriate CNS imaging ( Figure 2 and Figure 3 ). Nowadays, in context of the COVID-19 pandemic, prevalent risk factors, such as diabetes, especially decompensated [ 4 , 5 , 6 , 8 , 17 , 20 ], and most importantly the inappropriate use of steroids, has led to an increase of cases similar to the one presented herein [ 15 ]. For those patients with known risk factors such as diabetes, malignancies (particularly haematological), steroid use, neutropenia, HIV/AIDS, and immunosuppression in general, mucormycosis should always be considered in the differential diagnosis, in order to deliver prompt treatment [ 1 , 15 ].…”
Section: Discussionmentioning
confidence: 89%
“…Mucormycosis is also an important emerging condition among patients with haematological malignancies, allogeneic stem cell transplantation, and diabetes mellitus [ 4 ]. Historically, the inappropriate use of steroids has been linked with the development of this invasive fungal infection [ 5 , 6 ], particularly if associated with any of the abovementioned risk factors [ 7 , 8 ]. Moreover, inappropriate steroid use may trigger concurrent invasive fungal infections, such as concomitant mucormycosis and aspergillosis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%